Niche separation, ontogeny, and heterospecific alarm responses in centrarchid sunfish. (19th April 2018) - Xia, Jigang; Elvidge, Chris K; Cooke, Steven J
Abstract : Behavioral responses to risky information from both conspecific and heterospecific sources are important for mediating predation risk and can influence patterns of co-evolution and community trophic dynamics. We demonstrate that behavioral response patterns to chemical alarm cues in related fish species are highly plastic and may be closely related to ecological niche dynamics that shift with life history changes. Our findings open new research avenues into the role of the ecological niche in shaping fish behavioral phenotypes in response to risky public information. Abstract: Behavioral responses to alarm cues in aquatic species are typically examined with emphasis on the potential survival benefits accrued by conspecific receivers. By contrast, heterospecific responses to alarm cues and changes in responses with ontogeny in fishes are relatively unexplored. Taking an ecological niche perspective, we hypothesized that the response patterns of fish to risky chemical cues should be closely related to their degree of niche differentiation, which increases with ontogeny. We tested this hypothesis using the responses of adults from sympatric bluegill ( Lepomis macrochirus ) and pumpkinseed ( L. gibbosus ) populations to the alarm cues of conspecific and heterospecific adults and juveniles, including water as a control treatment. Responses measured consisted of changes in body posture (time spent with the dorsal fin <30°, between 30° and 60°, or >60°) and behavior (times spent still, frozen, at the surface, or on the bottom of the tank). Both adult bluegill and pumpkinseed spent significantly more time with their fins held >60° in response to adult versus juvenile alarm cues, with these responses mediated by donor species such that adult conspecific cues resulted in greater responses than heterospecific cues. The same general pattern was observed in the behavioral measures. These results demonstrate that behavioral response patterns to chemical alarm cues in sunfishes are highly plastic and are likely related to niche separation in adults. Our findings open new lines of research into the role of ecological niches in shaping behavioral responses of fish to risky information.